Respuestas

2013-12-24T18:04:20+01:00

 \frac{a+25}{b+35} = \frac{a}{b}
b(a + 25) = a(b + 35)
ab + 25b = ab + 35a
        25b = 35a
                            5b = 7a               (1)
                       3b - a = 160             (2)
    De (2)
                     a = 3b - 160              (2.1)
   (2.1) en (1)
                           5b = 7(3b - 160)
                           5b = 21b - 1120
                           21b - 5b = 1120
                                    16b = 1120
                                        b = 1120/16                     b = 70
En (1)
                 5(70) = 7a
                                        a = 5x70/7                        a = 50

                         a + b = 70 + 50 = 120   RESULTADO FINAL